El lesbianismo como monstruosidad en El cumpleaños de Alicia de Henry Díaz Vargas - Muñoz, Willy O. (Latin American Theatre Review, 2002)
This play enacts the celebration of a birthday party, which is dramatized following the cyclic and regenerative characteristics of the carnivalesque. The play is also based on the eternal struggle between thanatos and eros, proper of an erotic relationship, which, in this lesbian play, impels the lovers to kill each other. Lesbianism is a way of life that liberates women from patriarchal order. However, in Díaz’s play, the lesbian relationship is conceived as a monstrosity, as oppressive as the worse heterosexual relationship. My contention is that Díaz constructs female characters based on deforming fologocentric stereotypes that destine to death those who dare to stand outside the norm. (WOM, in Spanish)